Polypharmacy in Type 2 Diabetes Patients of the PROLANIS Program in Indonesia: Identification of Potential Drug-Drug Interaction - Lisni, Ida; Lestari, Keri; Andalusia, Lucia Rizka (Jordan Journal of Pharmaceutical Sciences, 2025)
The identification of potential drug-drug interactions (pDDIs) becomes critical in evaluating medication safety among diabetes mellitus patients. This study aimed to identify the pDDIs of polypharmacy in type 2 diabetes mellitus (T2D) patients of the Chronic Disease Management Program or Program Pengelolaan Penyakit Kronis (PROLANIS) Program. The T2D patients aged ≥18 were selected consecutively. A total sample of prescriptions containing ≥5 drugs was included. The mean age of patients was 62.70 ± 9.85 years (range 24–92 years), 62% were elderly, and 56.8% were females. Polypharmacy prescriptions were most prevalent in the Internal Medicine Department (92.8%). Of the 250 prescriptions, approximately 78.4% contained at least one pDDI. A total of 515 pDDIs were identified, with a median of 2 pDDIs per patient. Of these, 89.7% were of moderate severity. The drug pairs involved in moderate-severity pDDIs were glimepiride-metformin, glimepiride-bisoprolol, and metformin-ramipril. The number of drugs per prescription is a significant predictor of pDDIs (aOR = 7.48; 95% CI = 1.73-32.32). Subsequent analysis revealed that prescriptions containing eight or more drugs were 4.31 times more likely to have more than five pDDIs (p=0.010). Pharmacists must play a pivotal role in managing chronic disease medication to reduce drug interaction risks. This study suggests developing a digital system for healthcare professionals to improve patient medication safety.